KEMAMPUAN RHIZOPUS UNTUK MENURUNKAN KANDUNGAN SIANIDA DAN MENINGKATKAN KANDUNGAN PROTEIN SINGKONG (MANIHOT ESCULENTA CRANTZ) - Almasyhuri, Almasyhuri (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2015)
ABSTRACT Rhizopus oligosporus has been proven in reducing cyanogenic glucoside and increasing protein content of cassava which boiling and frying process can not do. However other Rizhopus strains are still unknown. The aim of the study was to determine the ability of three Rhizopus strains R. oligosporus MS5, R.oryzae F1, and R. oryzae EN in reducing cyanide and increasing protein content in bitter and sweet cassava fermentation added with nitrogen source. Cassavas was process to be flour. The flour was used as fermentation substrate by adding nitrogen or distilled water, then it was fermented with R. oligosporus MS5, R.oryzae F1, and R. oryzae EN in petri dish at 280C for 30 hours. After fermentation, contentof water, cyanide and protein in the fermented substrate were performed. Three strains of mold have the same ability to decrease cyanide, but the ability to increase protein content were varied. Without adding nitrogen, protein content increased 5.4 and 2.5 foldby R.oryzae F1 fermentation and by R. oryzae EN respectively. The addition of nitrogen protein content in the substarte increased 6.0 fold by R. oryzae F1 , 8.6 by R. oryzae EN and 2 by MS5 R.oligosporus. Three Rhizopus strains showed in reducing cyanide and improve protein content of cassava Keywords: bitter-cassava, cyanide, fermentation, protein, Rhizopus sp. ABSTRAK Rhizopus oligosporus terbukti dapat menurunkan kandungan sianida dan meningkatkan kandungan protein singkong tetapi strain lainnya belum diketahui. Penelitian ini menguji kemampuan R. oligosporus MS5, R. oryzae F1, dan R. oryzae EN dalam menurunkan kadar sianida dan meningkatkan kadar protein pada fermentasi substrat singkong. Singkong dibuat tepungdan hasilnya dibuat substrat fermentasi yang selanjutnya difermentasi dengan ketiga kapang dalam cawan petri pada suhu 280 C selama 30 jam. Kandungan air, sianida dan protein pada substrat dilakukan pada saat sebelum dan setelah difermentasi. Ketiga jenis kapang mempunyai kemampuan yang sama dalam penurunan kandungan sianida, tetapi kemampuan masing-masing kapang berbeda dalam meningkatkan kandungan protein. Tanpa penambahan sumber nitrogen, kapang R.oryzae F1 meningkatkan kandungan protein 5,4 kali dan R. oryzae EN 2,5 kali. Penambahan sumber nitrogen dapat meningkatkan kandungan protein, masing-masing kapang R. oryzae F1 meningkatkan kandungan protein 6,0 kali R. oryzae EN 8,6 kali dan R. oligosporus MS5 2 kali. Ketiga strain Rhizopus, yaitu R. oligosporus MS5, R. oryzae F1, dan R. oryzae EN dapat menghilangkan kandungan sianida dalam substrat singkong meningkatkan kandungan. Kemampuan R. oryzae EN dalam meningkatkan protein adalah paling tinggi, disusul R. oryzae F1, sedangkan kemamuan R oligosporus MS5 adalah yang paling rendah. Larutan sumber nitrogen yang ditambahkan pada substrat fermentasi Rhizopus dapat meningkatkan kadar protein [Penel Gizi Makan 2013, 36(2): 141-148] Kata kunci: fermentasi, protein Rhizopus, singkong-pahit, sianida